Cell surface properties of Phenol-Utilizing Bacteria Isolated from petroleum refinery wastewater - CE, Nwanyanwu; CS, Alisi; CO, Nweke; JC, Orji (Journal of Research in Biology, 2012)
Cell surface hydrophobicity of six phenol-utilizing bacteria isolated from Port Harcourt Petroleum refinery wastewater was assessed via bacterial adhesion to hydrocarbon (BATH), salt aggregation test (SAT) and Congo red binding (CRB) assays. The test organisms exhibited high to moderate hydrophobicity with BATH assay respectively when n-octane and p-xylene were employed. Bacillus sp. RBD, Escherichia coli. OPWW, Corynebacterium sp. DP, Citrobacter sp. RW and Pseudomonas sp. SD showed moderate hydrophobicity in SAT assay. On the other hand, Pseudomonas sp. RWW showed high hydrophobicity in SAT assay. Similar results of moderate hydrophobicity were obtained with CRB except Corynebacterium sp. DP that exhibited high hydrophobicity value of 14.70±1.00μg. The results obtained in this study showed that the isolates are mainly moderately hydrophobic which make them good candidates in the clean up activity of organic pollutants in polluted sites.